Empirical Test of Macroeconomic Variables and Stock Market Returns in Asian Emerging Market - Selamat, Zarehan (2001)
There has been a number of documented evidence examining the relationship between macroeconomic variables and stock returns in developed countries. However, the effect of changes in macroeconomic variables on Asian stock markets is an interesting area to research with, therefore there is a need to address such issue in these developing countries. This study attempts to investigate the relationships among stock prices, exchange rates, interest rates, trade balances, expected inflation, industrial production and money supply, by using data from six selected Asian countries namely Hong Kong, Singapore, Malaysia, Thailand, Philippines and Indonesia. The Multi index model (MIM) and the Error Correction Model (ECM) were applied to capture the dynamic relationship among these variables over the period of 1 990- 1 to 2000-4. The analysed were divided into two specifications -efficient market (Hong Kong, Singapore and Malaysia) and the less efficient market (Thailand, Philippines and Indonesia). The empirical results of this study indicate that consistent with many studies in developed markets, stock prices and macroeconomic variables are integrated in the long run. However in the short run, the results are country specific. The general performance of Hong Kong market is caused by interest rates and money supply. For Singapore, the results showed that trade balances, interest rates and money supply were the factors for stock pricing. Interest rates, exchange rates and money supply appeared to be the factors influencing the stock price fluctuations in Malaysia. While for Philippines the results indicated that stock prices are affected by lag exchange rate, lag trades balances and lag interest rates. For Thailand the results found that expected inflation, exchange rate and interest rate were the factors for stock pricing. For Indonesia, the finding showed that interest rates and money supply were dominant factors in pricing stock returns. Overall, for the efficient market the findings found that interest rates and money supplies appeared to be the major common factors affecting stock price fluctuations. However, in the less efficient market, the result indicated that interest rates were the only common factor affecting prices in Thailand, Philippines and Indonesia stock market. The results documented in this study provide better insights on the relationship between stock markets and major economic variables in selected Asian countries. Such evidence, lead to better decisions for investors with cross border investments and to policy marker on how to adjust policies in order to minimize stock prices volatility subsequently improve market's performance. These findings raise several important implications for stabilizing the stock market. Firstly, the result appeared to suggest country specific macroeconomic variables influencing stock markets and secondly, there was one or two common macro economic variables influencing the Asian countries.